The impact of anthropology on “Six Characters in Search of an Author”, the great Italian play by Luigi Pirandello - Kamarzadeh, Sepideh (Revista Hipótese, 2016)
Pirandello, in his theater writing and acting, not only did not restrict or control his attitudes, but also described the actor, in his novel “Si gira” (1915), “as if in exile - exiled not only from the stage, but also from himself.” In this study attempted is made to survey anthropology within the play thorough some factors like absurdism, existentialism, psychoanalysis, metaphor, and fascism in Six Characters in Search of an Author, a play of great Italian writer, Luigi Pirandello.
Keywords: Six Characters in Search of an Author; Luigi Pirandello; absurd; existential philosophy